Legal Aspects of Contracts in Digital Transactions Through E-Commerce Shopee With QRIS Payment Method - Nimrod; Tri Susanti; Sinaga, Irene Puteri A. S. (Global Action and Education for Society, 2025)
The development of digital technology has transformed the way society conducts transactions, especially through e-commerce platforms like Shopee. One of the increasingly popular payment methods is the Quick Response Code Indonesian Standard (QRIS), which offers convenience and efficiency in transactions. However, behind this convenience, the legal aspects of contractual obligations in digital transactions are often overlooked, even though they play a crucial role in ensuring legal certainty for the parties involved. This study aims to analyze the legal aspects of contractual obligations that arise in digital transactions using the QRIS payment method on Shopee. The discussion covers the rights and obligations of the parties in the transaction, the legal implications of contractual obligations in electronic contracts, consumer protection against potential risks such as fraud or breach of contract, and the available dispute resolution mechanisms. This study employs a normative juridical method with a regulatory approach, legal doctrines, and relevant case studies. The findings indicate that although digital transactions using QRIS have a legal basis in Indonesian regulations, challenges remain in implementing effective consumer protection and dispute resolution. Therefore, strengthening regulations and raising legal awareness among the public and business actors are necessary to create a secure and reliable digital transaction ecosystem.